Cybersecurity In Small and Medium Logistics Companies in Poland - Adam LASKA (Communications of International Proceedings, 2022)
The article analyzes the role and importance of cyber security for small and medium-sized logistics companies in Poland. The analysis focuses on the essence and scope of cybersecurity at the level of a logistics company and the ways of perceiving the role and importance of cyber risks and threats in management systems. The methods of approaching incidents of breaching the cybersecurity of companies, the methods used in companies to counteract these incidents, and the methods used after the occurrence of such an incident to restore the routine functioning of the company were analysed. The focus was also on the factors that the management considers to be the main limitations in introducing a modern and effective cybersecurity system. The aim of the study was to diagnose current trends and approaches of logistics companies in Poland in the field of cybersecurity. The study was conducted by means of questionnaire interviews in small (companies employing up to 49 people) and medium-sized (companies employing 50-249 people) logistics companies, represented by persons responsible for managing the cybersecurity area (directors, presidents, board members, IT specialists). The study was conducted on a sample of 230 logistics organizations in the first half of 2022. The results of the study lead to the conclusion that in small and medium-sized logistics companies in Poland, cybersecurity managers still focus on the simplest security measures for IT systems. This indicates that the real level of security in the sector is low. There is still a widespread belief among managers that expenditures on professional infrastructure ensuring cyber security are too high. Meanwhile, ensuring the security of the company's digital resources results primarily from organizational issues within the entity and from the knowledge of national and international legal regulations in the field of data digitization. Creating a cybersecurity strategy from a legal point of view makes the company better prepared to deal with threats.
Keywords: cyber security; supply chain security; cyber threats; small and medium enterprises